Integrating Emerging Technologies in Construction: Exploring Industry Awareness and Adoption - Shaza Rina Sahamir; Raja Rafidah Raja Muhd Rooshdi; Noor Akmal Adillah Ismail; Mohd Arif Marhani (Online Journal for TVET Practitioners, 2025)
The construction industry is undergoing significant transformation due to the integration of emerging technologies. However, awareness and adoption of these technologies may be limited, preventing broader application and full potential. A lack of adequate knowledge hinders the industry’s ability to harness these technologies for improving construction processes. This study aims to assess the awareness and adoption of emerging technologies among key players in the construction industry. By identifying which technologies are well-known and which remain unfamiliar, the research seeks to analyze the most prevalent and widely recognized emerging technologies in the construction industry. A quantitative research approach was employed, using a probability sampling technique. A total of 120 questionnaires were distributed to participants within the construction industry, with 75 responses returned and analyzed. The data were summarized using nominal and interval scales and analyzed through frequency and descriptive analysis. The findings reveal significant variation in the awareness of emerging technologies among respondents. Technologies such as Drones, Building Information Modeling (BIM), and Radio Frequency Identification (RFID) are among the most recognized, reflecting higher levels of familiarity within the industry. Conversely, technologies like Blockchain and Digital Twin are less well-known, indicating a gap in awareness. Overall, the study finds that respondents’ knowledge of emerging technologies is predominantly at a basic to average level, with limited advanced understanding. By focusing on increasing awareness of lesser-known technologies and enhancing overall technological literacy, the construction industry can better leverage emerging technologies to improve practices and performances.